Genetic mutation and its effect on craniofacial morphology in Malaysian family with class III malocclusion - Nowrin, Shifat A; Basri, Rehana; Alam, Mohammad Khursheed; Jaafar, Saidi; Mokhtar@Makhtar, Khairani Idah (2017)
Objectives: Class III malocclusion is a dominant inherited, slowly progressive dento-skeletal disharmony. It is characterized by over growth of mandible, stunted growth of maxilla, or a combination of both. The aetiology of class III malocclusion and the role of genes in this phenotype remain indistinct. The main objective of this study was to determine the DUSP6 gene mutation in three generations of a Malaysian Malay family having class III malocclusion and to conduct their cephalometric analyses. Methods: Genetic analyses of DUSP6 gene were carried out in a family with three individuals representing three generations 30 healthy control. Cephalometric radiographs were obtained from class III malocclusion subjects and pre-determined cephalometric linear and angular measurements were performed using Romexis software. t-test was used to analyse the cephalometric measurements compared with the cephalometric norm for class III malocclusion in Malaysia. Results: a heterozygous missense mutation c.1094C>T (p. Thr 365 Ile) was identified in DUSP6 gene in all three members of the family with class III malocclusion. Whereas, no mutation found in control group. t-tests showed significant differences in angular measurements Co-Gn-B and SN-MP variables in mutation group compared to the class III malocclusion norm. Conclusions: The outcome of this study broadened the mutation spectrum of class III malocclusion and the importance of DUSP6 gene in craniofacial morphology.